Caso dermatológico - Carvalho,Sandrina (2013)
The Fox-Fordyce disease represents an infrequent chronic pruritic skin rash of unknown etiology caused by obstruction of apocrine glands. Clinically it is characterized by multiple skin color and / or erythematous perifollicular papules in areas rich of apocrine glands (armpits, genital area, areolas and infra-mammary fold). Retinoids, antibiotics and topical immunomodulators have been used with varying results. We describe a case of a 16-year-old girl with Fox-Fordyce disease.